High-performance activated superfine slag powder for cement and preparation method of high-performance activated superfine slag powder
By using high-performance activated slag powder in silicate cement, the problem of excessive addition of slag powder affecting the strength of cement is solved, and the effect of improving compressive and flexural strength and reducing settling time is achieved.
Patent Information
- Application Number
- CN202411835128.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-18
AI Technical Summary
When applying slag micro powder to silicate cement, a large amount of addition will affect the strength of silicate cement, especially the compressive strength and flexural strength.
A preparation method is adopted to form a porous structure by treating the slag micropowder in aqueous hydrochloric acid solution, then loading silica on its surface and pores, and introducing a variety of active groups through grafting reaction to form a high-performance activated slag micropowder.
It significantly improves the compressive strength and flexural strength of silicate cement, reduces the settling time, and makes the silicate cement show the advantages of high compressive strength, high flexural strength and short settling time, improving construction efficiency and durability sex.
Smart Images

Figure BDA0005186490420000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of slag micropowder, and more specifically, to a high-performance activated slag micropowder for cement and a preparation method thereof. Background Art
[0002] Slag powder is a powdery substance obtained by crushing slag produced in the production of metallurgy, construction and other industries. It is also one of the important industrial by-products. Since the chemical composition of slag powder mainly includes oxides such as SiO2, CaO, Al2O3, MgO, Fe2O3, and a small amount of CaS, MnS, etc., it is often used in Portland cement. Specifically: slag powder is added to Portland cement clinker and combined with gypsum to obtain Portland cement, realizing the resource utilization of slag powder. However, when slag powder is applied to Portland cement, if the amount added is too much, it affects the strength of Portland cement. Summary of the invention
[0003] On the basis of applying slag powder to silicate cement, in order to improve the compressive strength and flexural strength of silicate cement, the present application provides a high-performance activated slag powder for cement and a preparation method thereof.
[0004] In the first aspect, the present application provides a method for preparing high-performance activated slag powder for cement, which adopts the following technical scheme: A method for preparing high-performance activated slag powder for cement mainly comprises the following steps: S1. Add slag powder to hydrochloric acid aqueous solution, stir for 20-40 minutes, filter, and obtain porous slag powder; S2, mixing an alcohol solvent and tetraethyl orthosilicate, adding porous slag powder, stirring for 50-70 minutes, and obtaining a solid-liquid mixture; S3, adding the solid-liquid mixture to the alcohol-water mixture, stirring for 50-70 minutes, adjusting the pH value to 7-8, stirring for 10-30 minutes, filtering, and obtaining silicon-loaded slag powder; S4, mixing water and silicon-loaded slag powder, adding 3-(methacryloyloxy)propyltrimethoxysilane, stirring for 1-3 hours, filtering, and obtaining grafted silicon-loaded slag powder; S5. Mix the alcohol solvent and the grafted silicon-loaded slag powder, add sucrose oleate, La-phosphatidylcholine, and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, add an organic initiator, stir for 2-4 hours, filter, wash, and dry to constant weight to obtain high-performance activated slag powder.
[0005] Optionally, the weight ratio of the slag powder, tetraethyl orthosilicate, 3-(methacryloyloxy)propyltrimethoxysilane, sucrose oleate, La-phosphatidylcholine, and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate is 100:(14-16):(7-9):(4-6):(4-6):(1-3).
[0006] The high-performance activated slag powder obtained by the preparation method of the present application is applied to silicate cement, which effectively improves the compressive strength and flexural strength of silicate cement and reduces the setting time. The 28d compressive strength is greater than 61MPa, the 28d flexural strength is greater than 8MPa, the initial setting time is less than 70min, and the final setting time is less than 180min. The silicate cement exhibits the advantages of high compressive strength, high flexural strength and short setting time, thereby improving construction efficiency, shortening construction period, enhancing durability and service life, and meeting market demand.
[0007] The preparation method of the present application first uses a hydrochloric acid aqueous solution to treat slag powder to obtain porous slag powder, improve the pore structure of slag powder, increase the porosity and surface area of slag powder, and improve the adsorption effect. Then, ethyl orthosilicate is adsorbed on the surface and pores of porous slag powder, and it is hydrolyzed under the action of water, and silica is loaded on the pores and surface of porous slag powder to obtain silicon-loaded slag powder, which effectively increases the surface active sites of slag powder and improves activity. After that, 3-(methacryloyloxy)propyltrimethoxysilane is grafted on the silicon-loaded slag powder to introduce a carbon-carbon double bond. Further, under the action of an organic initiator, a polymerization reaction is used to graft sucrose oleate, La-phosphatidylcholine, and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate on the silicon-loaded slag powder to obtain high-performance slag powder. At this time, the surface and pores of high-performance slag powder contain a large amount of silicon dioxide, as well as a large number of active groups such as siloxy, ester, hydroxyl, epoxy, phosphate, quaternary ammonium, pyridine, and amine. The synergistic effect between them is used to improve the dispersibility and binding force of high-performance activated slag powder and enhance surface activity. In addition, high-performance slag powder is applied to silicate cement to improve dispersion stability, fluidity, density, compressive strength and flexural strength, and setting time, so that silicate cement exhibits better durability and stability in use.
[0008] Optionally, the weight ratio of the slag powder and the organic initiator is 100:(0.2-0.5).
[0009] By adopting the above technical solution, the addition amount of the organic initiator is limited, the stability of the polymerization reaction is ensured, the grafting stability is enhanced, and the stability of the high-performance activated slag micropowder is guaranteed.
[0010] Optionally, the weight ratio of the slag powder to the hydrochloric acid aqueous solution is 10:(25-35), and the mass concentration of the hydrochloric acid aqueous solution is 3-8%.
[0011] By adopting the above technical solution, the amount of hydrochloric acid aqueous solution added is limited, and the hydrochloric acid aqueous solution can effectively increase the porosity of slag micropowder, enhance the modification effect of porous slag micropowder, improve the compressive strength and flexural strength of silicate cement, and reduce the setting time of silicate cement. In multiple embodiments, the mass concentration of the hydrochloric acid aqueous solution is 6%, and the mass concentration can also be set to 3%, 4%, 5%, 7%, and 8% as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0012] Optionally, the weight ratio of the slag powder, the alcohol solvent in step S2, and the alcohol-water mixture is 10:(45-55):(45-55), and the mass concentration of alcohol in the alcohol-water mixture is 10-20%.
[0013] By adopting the above technical scheme, the addition amount of the alcohol solvent in step S2 is limited to ensure the uniformity of the dispersion of porous slag powder, so as to facilitate the adsorption of ethyl orthosilicate on the pores and surface of porous slag powder. The addition amount of the alcohol-water mixture is also limited to facilitate the mixing of the alcohol-water mixture and the solid-liquid mixture, improve the use effect of high-performance activated slag powder, and improve the mechanical properties of silicate cement. In multiple embodiments, the mass concentration of alcohol in the alcohol-water mixture is 15%, and the mass concentration can also be set to 10%, 12%, 18%, 20% as needed, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Optionally, the alcohol in the alcohol-water mixture is one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, n-hexanol, n-heptanol, and cyclohexanol.
[0015] Optionally, the weight ratio of the slag powder, water, and the alcohol solvent in step S5 is 1:(7-13):(7-13).
[0016] By adopting the above technical scheme, the amount of water added in step S4 is limited to ensure the uniformity of the dispersion of the silicon-loaded slag powder, and facilitate the grafting of 3-(methacryloyloxy)propyltrimethoxysilane. The amount of alcohol solvent added in step S5 is also limited to ensure the uniformity of the dispersion of the grafted silicon-loaded slag powder, and facilitate the grafting reaction of sucrose oleate, La-phosphatidylcholine, and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, ensuring the stability and use effect of the high-performance activated slag powder.
[0017] Optionally, the organic initiator is one or more of benzoyl peroxide, diisopropyl peroxydicarbonate, tert-butyl perbenzoate, di-tert-butyl peroxide, and azobisisobutyronitrile.
[0018] By adopting the above technical solution, the organic initiator is limited, which facilitates the selection of the organic initiator.
[0019] Optionally, the alcohol solvent is one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, n-hexanol, n-heptanol, and cyclohexanol.
[0020] By adopting the above technical scheme, the alcohol solvent is limited, which facilitates the selection of the alcohol solvent, increases the uniformity of the raw material mixture, facilitates the grafting reaction, enhances the modification effect, and improves the performance and stability of the high-performance activated slag micropowder.
[0021] Optionally, in step S3, the pH value is adjusted to 7-8 using a sodium hydroxide aqueous solution, and the mass concentration of the sodium hydroxide aqueous solution is 20-30%. In multiple embodiments, the mass concentration of the sodium hydroxide aqueous solution is 25%, and the mass concentration can also be set to 20%, 22%, 28%, 30% as needed, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] Optionally, the average particle size of the slag powder is 1-20 μm.
[0023] By adopting the above technical solution, the average particle size of slag powder is limited, the stability of the source of slag powder is ensured, the fluidity of silicate cement is improved, the uniformity of the dispersion of high-performance active slag powder in silicate cement is ensured, and the mechanical properties of silicate cement are enhanced. In multiple implementation schemes, the average particle size of slag powder is 4 μm, and the average particle size can also be set to 1 μm, 5 μm, 10 μm, 15 μm, 20 μm as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] In a second aspect, the present application provides a high-performance activated slag powder for cement, which adopts the following technical scheme: a high-performance activated slag powder for cement, wherein the high-performance activated slag powder is prepared by the preparation method of the high-performance slag powder for cement.
[0025] In a third aspect, the present application provides a silicate cement, which adopts the following technical solution: A silicate cement is mainly prepared from the following raw materials in parts by weight: 500-700 parts of silicate cement clinker, 300-500 parts of high-performance activated slag micropowder, 30-50 parts of fly ash, and 30-50 parts of desulfurized gypsum; the high-performance activated slag micropowder is prepared by the preparation method of high-performance slag micropowder for cement.
[0026] By adopting the above technical scheme, the raw materials and raw material ratio of silicate cement are optimized, which is convenient for the preparation of silicate cement, improves the mechanical properties of silicate cement, reduces the setting time of silicate cement, and facilitates construction.
[0027] In summary, this application has at least the following beneficial effects: The high-performance activated slag powder obtained by the preparation method of this application uses hydrochloric acid aqueous solution to improve the pore structure, load silica, increase active sites, improve activity, graft 3-(methacryloyloxy)propyltrimethoxysilane, sucrose oleate, La-phosphatidylcholine, 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, introduce a large number of active groups such as siloxy, ester, hydroxyl, epoxy, phosphate, quaternary ammonium, pyridine, and amine to improve dispersibility and binding force and enhance surface activity. It is applied to silicate cement, making the 28d compressive strength of silicate cement greater than 61MPa, the 28d flexural strength greater than 8MPa, the initial setting time less than 70min, and the final setting time less than 180min, showing the advantages of high compressive strength, high flexural strength, and short setting time, improving construction efficiency, shortening construction period, enhancing durability and service life, and improving the use effect of high-performance activated slag powder to meet market demand. DETAILED DESCRIPTION
[0028] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified. Example
[0029] Example 1 A high-performance activated slag powder for cement, the preparation method of which mainly comprises the following steps: S1. Add 100 g of slag powder to 300 g of 6% hydrochloric acid aqueous solution at a stirring rate of 300 r / min, stir for 30 min, and then filter to obtain porous slag powder.
[0030] Among them, the average particle size of the slag micropowder is 4μm, and the SiO2 content of the slag micropowder is 38%, the CaO content is 34%, the Al2O3 content is 14%, the MgO content is 8%, and the Fe2O3 content is 2%.
[0031] S2. Add 15 g of tetraethyl orthosilicate to 500 g of alcohol solvent at a stirring rate of 300 r / min, and stir for 3 min. Add the porous slag powder obtained in step S1, and stir for 60 min to obtain a solid-liquid mixture.
[0032] Wherein, the alcohol solvent is ethanol.
[0033] S3. Add the solid-liquid mixture obtained in step S2 to 500 g of alcohol-water mixture at a stirring rate of 300 r / min, and stir for 60 min. Then adjust the pH value to 7.5 with a sodium hydroxide aqueous solution having a mass concentration of 25%, and stir for 20 min. Then filter to obtain silicon-loaded slag powder.
[0034] The alcohol-water mixture is an ethanol-water mixture, and the mass concentration of ethanol in the ethanol-water mixture is 15%.
[0035] S4. Add the silicon-loaded slag powder obtained in step S3 to 1000 g of water at a stirring rate of 300 r / min, and stir for 3 min. Add 8 g of 3-(methacryloyloxy)propyltrimethoxysilane, and stir for 2 h. Then filter to obtain grafted silicon-loaded slag powder.
[0036] S5. Add the grafted silicon-loaded slag powder obtained in step S4 to 1000g of alcohol solvent at a stirring rate of 300r / min, and stir for 3min. Add 5g of sucrose oleate, 5g of La-phosphatidylcholine, and 2g of 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, and stir for 3min. Add 0.3g of organic initiator, and stir for 3h. Then filter, wash twice with 30% ethanol-water mixture, and use 300g of ethanol-water mixture each time, and dry to constant weight to obtain high-performance activated slag powder.
[0037] Wherein, the alcohol solvent is ethanol; and the organic initiator is diisopropyl peroxydicarbonate.
[0038] Example 2 A high-performance activated slag powder for cement, the preparation method of which mainly comprises the following steps: S1. Add 100 g of slag powder to 250 g of 6% hydrochloric acid aqueous solution at a stirring rate of 300 r / min, stir for 20 min, and then filter to obtain porous slag powder.
[0039] Among them, the average particle size of the slag micropowder is 4μm, and the SiO2 content of the slag micropowder is 38%, the CaO content is 34%, the Al2O3 content is 14%, the MgO content is 8%, and the Fe2O3 content is 2%.
[0040] S2. Add 14 g of tetraethyl orthosilicate to 450 g of alcohol solvent at a stirring rate of 300 r / min, and stir for 3 min. Add the porous slag powder obtained in step S1, and stir for 50 min to obtain a solid-liquid mixture.
[0041] Wherein, the alcohol solvent is ethanol.
[0042] S3. Add the solid-liquid mixture obtained in step S2 to 550 g of the alcohol-water mixture at a stirring rate of 300 r / min, and stir for 70 min. Then adjust the pH value to 7 with a sodium hydroxide aqueous solution having a mass concentration of 15%, and stir for 10 min. Then filter to obtain silicon-loaded slag powder.
[0043] The alcohol-water mixture is an ethanol-water mixture, and the mass concentration of ethanol in the ethanol-water mixture is 15%.
[0044] S4. Add the silicon-loaded slag powder obtained in step S3 to 700 g of water at a stirring rate of 300 r / min, and stir for 3 min. Add 7 g of 3-(methacryloyloxy)propyltrimethoxysilane, and stir for 1 h. Then filter to obtain grafted silicon-loaded slag powder.
[0045] S5. Add the grafted silicon-loaded slag powder obtained in step S4 to 700g of alcohol solvent at a stirring rate of 300r / min, and stir for 3min. Add 6g of sucrose oleate, 4g of La-phosphatidylcholine, and 3g of 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, and stir for 3min. Add 0.5g of organic initiator, and stir for 4h. Then filter, wash twice with 30% ethanol-water mixture, and use 300g of ethanol-water mixture each time, and dry to constant weight to obtain high-performance activated slag powder.
[0046] Wherein, the alcohol solvent is ethanol; and the organic initiator is diisopropyl peroxydicarbonate.
[0047] Example 3 A high-performance activated slag powder for cement, the preparation method of which mainly comprises the following steps: S1. Add 100 g of slag powder to 350 g of 6% hydrochloric acid aqueous solution at a stirring rate of 300 r / min, stir for 40 min, and then filter to obtain porous slag powder.
[0048] Among them, the average particle size of the slag micropowder is 4μm, and the SiO2 content of the slag micropowder is 38%, the CaO content is 34%, the Al2O3 content is 14%, the MgO content is 8%, and the Fe2O3 content is 2%.
[0049] S2. Add 16 g of tetraethyl orthosilicate to 550 g of alcohol solvent at a stirring rate of 300 r / min, and stir for 3 min. Add the porous slag powder obtained in step S1, and stir for 70 min to obtain a solid-liquid mixture.
[0050] Wherein, the alcohol solvent is ethanol.
[0051] S3. Add the solid-liquid mixture obtained in step S2 to 450 g of the alcohol-water mixture at a stirring rate of 300 r / min, and stir for 50 min. Then adjust the pH value to 8 with a sodium hydroxide aqueous solution having a mass concentration of 25%, and stir for 30 min. Then filter to obtain silicon-loaded slag powder.
[0052] The alcohol-water mixture is an ethanol-water mixture, and the mass concentration of ethanol in the ethanol-water mixture is 15%.
[0053] S4. Add the silicon-loaded slag powder obtained in step S3 to 1300 g of water at a stirring rate of 300 r / min, and stir for 3 min. Add 9 g of 3-(methacryloyloxy)propyltrimethoxysilane, and stir for 3 h. Then filter to obtain grafted silicon-loaded slag powder.
[0054] S5. Add the grafted silicon-loaded slag powder obtained in step S4 to 1300g of alcohol solvent at a stirring rate of 300r / min, and stir for 3min. Add 4g of sucrose oleate, 6g of La-phosphatidylcholine, and 1g of 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, and stir for 3min. Add 0.2g of organic initiator, and stir for 2h. Then filter, wash twice with 30% ethanol-water mixture, and use 300g of ethanol-water mixture each time, and dry to constant weight to obtain high-performance activated slag powder.
[0055] Wherein, the alcohol solvent is ethanol; and the organic initiator is diisopropyl peroxydicarbonate.
[0056] Comparative Example Comparative Example 1 A high-performance activated slag powder for cement, which is different from Example 1 in that steps S4-S5 are different.
[0057] Steps S4-S5 are specifically as follows: the silicon-loaded slag powder obtained in step S3 is washed twice with a 30% ethanol-water mixture, with 300 g of the ethanol-water mixture used each time, and dried to constant weight to obtain high-performance activated slag powder.
[0058] Comparative Example 2 A high-performance activated slag powder for cement, which is different from Example 1 in that in step S5, sucrose oleate, La-phosphatidylcholine, and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate are replaced with an equal amount of 3-(methacryloyloxy)propyltrimethoxysilane. That is, in step S5, the amount of 3-(methacryloyloxy)propyltrimethoxysilane added is 12 g.
[0059] Comparative Example 3 A high-performance activated slag powder for cement, which is different from Example 1 in that in step S5, La-phosphatidylcholine and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate are replaced with an equal amount of sucrose oleate. That is, in step S5, the amount of sucrose oleate added is 12g.
[0060] Comparative Example 4 A high-performance activated slag powder for cement, which is different from Example 1 in that in step S5, sucrose oleate and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate are replaced with equal amounts of La-phosphatidylcholine. That is, in step S5, the amount of La-phosphatidylcholine added is 12 g.
[0061] Comparative Example 5 A high-performance activated slag powder for cement, which is different from Example 1 in that in step S5, sucrose oleate and La-phosphatidylcholine are replaced with an equal amount of 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate. That is, in step S5, the amount of 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate added is 12g.
[0062] Comparative Example 6 A high-performance activated slag powder for cement, which is different from Example 1 in that, in step S5, 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate is replaced with equal amounts of sucrose oleate and La-phosphatidylcholine, and the weight ratio of sucrose oleate and La-phosphatidylcholine is 1:1. That is, in step S5, the addition amount of sucrose oleate is 6g, and the addition amount of La-phosphatidylcholine is 6g.
[0063] Comparative Example 7 A high-performance activated slag powder for cement, which is different from Example 1 in that, in step S5, La-phosphatidylcholine is replaced with equal amounts of sucrose oleate and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, and the weight ratio of sucrose oleate and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate is 5:2. That is, in step S5, the addition amount of sucrose oleate is 8.57g, and the addition amount of 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate is 3.43g.
[0064] Comparative Example 8 A high-performance activated slag powder for cement, which is different from Example 1 in that, in step S5, sucrose oleate is replaced with equal amounts of La-phosphatidylcholine and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, and the weight ratio of La-phosphatidylcholine and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate is 5:2. That is, in step S5, the addition amount of La-phosphatidylcholine is 8.57g, and the addition amount of 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate is 3.43g.
[0065] Application Examples Application Example 1 A silicate cement is prepared from the following raw materials: 600g of silicate cement clinker, 400g of high-performance activated slag powder, 40g of fly ash and 40g of desulfurized gypsum.
[0066] Among them, the C3S content in the silicate cement clinker is 38%, the C2S content is 42%, the C3A content is 3%, and the C4AF content is 15%; the fly ash is Class I fly ash; the desulfurized gypsum is selected from Shijiazhuang Deze Mineral Products Co., Ltd.; and the high-performance activated slag powder is prepared by the method of Preparation Example 1.
[0067] A method for preparing silicate cement mainly comprises the following steps: High-performance activated slag powder, fly ash and desulfurized gypsum were added to silicate cement clinker and stirred for 5 minutes to obtain silicate cement.
[0068] Application Example 2-3 A silicate cement, which is different from Application Example 1 in that the sources of high-performance activated slag powder in the raw materials of silicate cement are different, and the high-performance activated slag powder of Application Examples 2-3 are prepared by the methods of Examples 2-3 respectively.
[0069] Comparative Application Examples Comparative Application Examples 1-8 A silicate cement, which differs from Application Example 1 in that the sources of high-performance activated slag powder in the raw materials of silicate cement are different, and the high-performance activated slag powder of Comparative Application Examples 1-8 are prepared respectively by the methods of Comparative Examples 1-8.
[0070] Comparison example A silicate cement, which is different from Application Example 1 in that an equal amount of slag powder is used to replace high-performance activated slag powder in the raw materials of the silicate cement.
[0071] Performance Testing The silicate cement obtained from Application Examples 1-3, Comparative Application Examples 1-8, and Control Examples was taken respectively, and the 28d compressive strength, 28d flexural strength, initial setting time, and final setting time of the silicate cement were tested according to GB / T17671-2021 and GB / T1346-2011. The test results are shown in Table 1.
[0072] Table 1 Test results As can be seen from Table 1, the application of high-performance activated slag powder in silicate cement can significantly improve the compressive strength and flexural strength of silicate cement, with a 28d compressive strength of 61.37-63.87MPa and a 28d flexural strength of 8.96-9.38MPa, giving it better mechanical properties. It also significantly reduces the setting time of silicate cement, with an initial setting time of 66-68min and a final setting time of 171-176min, giving it a good setting time, improving construction efficiency, shortening the construction period, and meeting market demand.
[0073] Compare the control example and comparative application example 1. Comparative document 1 adds slag powder to silicate cement; Comparative application example 1 adds high-performance activated slag powder to silicate cement, and the slag powder is treated with ethyl orthosilicate to obtain it. It can be seen that the slag powder is modified and silica is loaded in the pores and surface of the slag powder, which can increase the compressive strength and flexural strength of silicate cement and reduce the setting time. Combined with comparative application example 2, comparative application example 1 adds high-performance activated slag powder to silicate cement, and the slag powder is treated with ethyl orthosilicate and 3-(methacryloyloxy)propyltrimethoxysilane to obtain it. It can be seen that on the basis of loading silica on the slag powder, further grafting its surface and introducing active groups can effectively improve the use effect of high-performance activated slag powder in silicate cement.
[0074] Comparative Application Examples 2-5 are compared. The high-performance activated slag powder of Comparative Application Example 2 is obtained by treating silicon-loaded slag powder with 3-(methacryloyloxy)propyltrimethoxysilane; the high-performance activated slag powder of Comparative Application Example 3 is obtained by treating 3-(methacryloyloxy)propyltrimethoxysilane and sucrose oleate dendrite silicon-loaded slag powder; the high-performance activated slag powder of Comparative Application Example 4 is obtained by treating silicon-loaded slag powder with 3-(methacryloyloxy)propyltrimethoxysilane and La-phosphatidylcholine; the high-performance activated slag powder of Comparative Application Example 5 is obtained by treating silicon-loaded slag powder with 3-(methacryloyloxy)propyltrimethoxysilane and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate. It can be seen from this that on the basis of grafting 3-(methacryloyloxy)propyltrimethoxysilane onto silicon-loaded slag powder, further grafting sucrose oleate alone, or grafting La-phosphatidylcholine alone, or grafting 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate alone can all improve the compressive strength and flexural strength of silicate cement and reduce the setting time, so that the high-performance activated slag powder exhibits better performance and use effect.
[0075] Comparative Application Examples 6-8 and Application Example 1 are compared. The high-performance activated slag powder of Comparative Application Example 6 is obtained by treating the grafted silicon-loaded slag powder with sucrose oleate and La-phosphatidylcholine; the high-performance activated slag powder of Comparative Application Example 7 is obtained by treating the grafted silicon-loaded slag powder with sucrose oleate and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate; the high-performance activated slag powder of Comparative Application Example 8 is obtained by treating the grafted silicon-loaded slag powder with La-phosphatidylcholine and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate; the high-performance activated slag powder of Application Example 1 is obtained by treating the grafted silicon-loaded slag powder with sucrose oleate, La-phosphatidylcholine and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate. It can be seen from this that on the basis of silicon-loaded slag powder grafted with 3-(methacryloyloxy)propyltrimethoxysilane, sucrose oleate, La-phosphatidylcholine, and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate are further grafted simultaneously, and active groups such as siloxy, ester, hydroxyl, epoxy, phosphate, quaternary ammonium, pyridine, and amine are introduced on the surface to improve the binding force and dispersibility of high-performance activated slag powder, so that the silicate cement exhibits better mechanical properties, and improves durability and service life.
[0076] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing high-performance activated slag powder for cement, characterized in that: The main steps are as follows: S1. Add slag powder to hydrochloric acid aqueous solution, stir for 20-40 minutes, filter, and obtain porous slag powder; S2, mixing an alcohol solvent and tetraethyl orthosilicate, adding porous slag powder, stirring for 50-70 minutes, and obtaining a solid-liquid mixture; S3, adding the solid-liquid mixture to the alcohol-water mixture, stirring for 50-70 minutes, adjusting the pH value to 7-8, stirring for 10-30 minutes, filtering, and obtaining silicon-loaded slag powder; S4, mixing water and silicon-loaded slag powder, adding 3-(methacryloyloxy)propyltrimethoxysilane, stirring for 1-3 hours, filtering, and obtaining grafted silicon-loaded slag powder; S5. Mix the alcohol solvent and the grafted silicon-loaded slag powder, add sucrose oleate, La-phosphatidylcholine, and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate, add an organic initiator, stir for 2-4 hours, filter, wash, and dry to constant weight to obtain high-performance activated slag powder.
2. The method for preparing high-performance activated slag powder for cement according to claim 1, characterized in that: The weight ratio of the slag powder, tetraethyl orthosilicate, 3-(methacryloyloxy)propyltrimethoxysilane, sucrose oleate, La-phosphatidylcholine, and 3-(2-amino-5-bromopyridin-3-yl)ethyl acrylate is 100:(14-16):(7-9):(4-6):(4-6):(1-3).
3. The method for preparing high-performance activated slag powder for cement according to claim 1, characterized in that: The weight ratio of the slag powder to the organic initiator is 100:(0.2-0.5).
4. The method for preparing high-performance activated slag powder for cement according to claim 1, characterized in that: The weight ratio of the slag powder to the hydrochloric acid aqueous solution is 10:(25-35), and the mass concentration of the hydrochloric acid aqueous solution is 3-8%.
5. The method for preparing high-performance activated slag powder for cement according to claim 1, characterized in that: The weight ratio of the slag powder, the alcohol solvent in step S2, and the alcohol-water mixture is 10:(45-55):(45-55), and the mass concentration of alcohol in the alcohol-water mixture is 10-20%.
6. The method for preparing high-performance activated slag powder for cement according to claim 1, characterized in that: The weight ratio of the slag powder, water, and the alcohol solvent in step S5 is 1:(7-13):(7-13).
7. The method for preparing high-performance activated slag powder for cement according to claim 1, characterized in that: The organic initiator is one or more of benzoyl peroxide, diisopropyl peroxydicarbonate, tert-butyl perbenzoate, di-tert-butyl peroxide, and azobisisobutyronitrile.
8. The method for preparing high-performance activated slag powder for cement according to claim 1, characterized in that: The alcohol solvent is one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol, n-hexanol, n-heptanol, and cyclohexanol.
9. The method for preparing high-performance activated slag powder for cement according to claim 1, characterized in that: The average particle size of the slag powder is 1-20 μm.
10. A high-performance activated slag powder for cement, characterized in that: The high-performance activated slag powder is prepared by the method for preparing high-performance slag powder for cement as claimed in any one of claims 1 to 9.